AMBRA1 and BECLIN 1 interplay in the crosstalk between autophagy and cell proliferation - Cianfanelli, Valentina (Cell Cycle, 2015)
Autophagy-promoting proteins and stimuli are often associated with inhibition of cell proliferation; in this context, we recently described a key role for the pro-autophagic protein AMBRA1. Indeed, AMBRA1, through its direct interaction with the protein phosphatase PP2A, tightly regulates the stability of the oncoprotein and pro-mitotic factor c-Myc. Moreover, the AMBRA1-mediated regulation of c-Myc affects both cell proliferation rate and tumorigenesis. Interestingly, AMBRA1/PP2A activity is under the control of the master regulator of autophagy and cell growth, the protein kinase mTOR. Besides the mechanistic details of this regulation pathway which we dissected previously, any possible interplay(s) between AMBRA1 and its interactor BECLIN 1 was not investigated in this scenario. Here we show that both AMBRA1 and BECLIN 1 affect c-Myc regulation, but through two different pathways. Nevertheless, these two pro-autophagic proteins are, together with PP2A, in the same macromolecular complex, whose functional significance of which will be addressed in future studies.